Second harmonic generation imaging of the deep shade plant Selaginella erythropus using multifunctional two-photon laser scanning microscopy - Reshak, A H; Sheue, C-R (Journal of microscopy, 2012)
BACKGROUND: Multifunctional two-photon laser scanning microscopy provides attractive advantages over conventional two-photon laser scanning microscopy. For the first time, simultaneous measurement of the second harmonic generation (SHG) signals in the forward and backward directions and two photon excitation fluorescence were achieved from the deep shade plant Selaginella erythropus. RESULTS: These measurements show that the S. erythropus leaves produce high SHG signals in both directions and the SHG signals strongly depend on the laser's status of polarization and the orientation of the dipole moment in the molecules that interact with the laser light. The novelty of this work is (1) uncovering the unusual structure of S. erythropus leaves, including diverse chloroplasts, various cell types and micromophology, which are consistent with observations from general electron microscopy; and (2) using the multifunctional two-photon laser scanning microscopy by combining three platforms of laser scanning microscopy, fluorescence microscopy, harmonic generation microscopy and polarizing microscopy for detecting the SHG signals in the forward and backward directions, as well as two photon excitation fluorescence. CONCLUSIONS: With the multifunctional two-photon laser scanning microscopy, one can use noninvasive SHG imaging to reveal the true architecture of the sample, without photodamage or photobleaching, by utilizing the fact that the SHG is known to leave no energy deposition on the interacting matter because of the SHG virtual energy conservation characteristic.
Keywords: Selaginellaceae; Plant Leaves; Chloroplasts; mikroskopie fluorescenční multifotonová; chloroplasty; Microscopy, Fluorescence, Multiphoton; konfokální mikroskopie; Microscopy, Confocal; listy rostlin; počítačové zpracování obrazu; Image Processing, Computer-Assisted